Pengaruh Efektivitas Pelaksanaan PPDB dan Mutu Layanan Pendidikan Terhadap Tingkat Kepuasan Wali Murid di MTs Negeri 1 & 2 Kota Serang - Siti Nur Ufudiah; Supardi; Machdum Bachtiar (Jurnal Multidisiplin Madani, 2022)
This study aims to describe the level of achievement of the effectiveness of the acceptance of new students, describe the level of achievement of service quality, and describe the level of achievement of the effect of the effectiveness of acceptance of new students and service quality on the level of satisfaction of parents of students. The research was conducted at Madrasah Tsanawiyah Negeri 1 and 2 Serang City. The study used quantitative methods with regression analysis. The results of the study found: First, the effectiveness of new student admissions is high, reaching 83%. Second, high service quality reaches 86%. Third, the satisfaction of the parents of the participants was high, reaching 83%. The effectiveness of PPDB affects the satisfaction of parents of students. Service quality affects the satisfaction of parents of students.